Integrated Model of a Family Approach and Local Support in Tuberculosis Case Finding Efforts in People with HIV/AIDS - Astutik, Erni; Wahyuni, Chatarina Umbul; Manurung, Imelda F E; Ssekalembe, Geofrey (UI Scholars Hub, 2021)
The human immunodeficiency virus (HIV) remains a major global public health problem. People with HIV/acquired immune deficiency syndrome (AIDS) are more susceptible to opportunistic infections such as tuberculosis (TB). Therefore, families and community leaders need to help monitor people living with HIV/AIDS (PLWHA). This study aimed to analyze an integrated family approach and local support model to detect TB cases in PLWHA. This study used a case-control study in Kupang City, East Nusa Tenggara Province, in July 2020. The sample comprised 100 people (50 PLWHA with TB case and 50 controls) using total sampling and random sampling, respectively. The variables related to TB case finding in PLWHA were family employment status, duration of HIV/AIDS, family knowledge of TB, and family support. The data were analyzed using multiple logistic regression. The families with PLWHA with an extended illness duration (OR = 0.81, 95% CI = 0.69–0.95, p-value = 0.01), families who did not work (OR = 3.31, 95% CI = 1.16 9.41, p-value = 0.025), families who had good knowledge (OR = 4.79, 95% CI = 1.70–13.51, p-value = 0.003), and families who provided good support (OR = 3.03, 95% CI = 1.05–8.76, p-value= 0.04) were better able to detect TB in PLWHA.